"It Just Depends on Their Stability": A Qualitative Examination of Patient Factors Influencing Providers' Contraceptive Counseling Approaches for Persons With Substance Use Disorders. Issue 1 (2nd January 2023) - Balto, Rwina; Brooks, Jennifer H.; Mayo, Rachel M.; Eichelberger, Kacey Y.; Charron, Elizabeth
Abstract : Objectives: This qualitative study examined how patient-related factors influence providers' contraceptive counseling for persons with substance use disorders (SUDs). Specifically, we explored individual behavior and social factors that contribute to providers modifying their contraceptive counseling approaches and described how providers alter their counseling recommendations and communication strategies in the presence of such factors. Methods: In 2019, we purposively recruited a national sample of contraceptive providers (N = 24) and conducted semistructured phone interviews to inquire about their contraceptive counseling practices for women with SUDs. Interviews were audio recorded, transcribed verbatim, and analyzed using thematic analysis with inductive codes. Results: Participants included 10 medical doctors, 8 nurse practitioners, and 6 certified nurse-midwives. We found that providers modify their contraceptive counseling provision when their patients are actively using substances or have unstable living conditions, such as intimate partner violence or homelessness. With patients experiencing these instabilities, providers reported postponing contraceptive discussions until patients are stabilized in treatment, recommending long-active reversible contraceptive methods, and varying communication styles according to their own perceptions of patients' communication needs. Providers perceived that individuals in long-term recovery have increased stability and fewer barriers to contraceptive access and adherence and therefore reported increased willingness to provide greater autonomy during contraceptive decision making and shift the counseling focus to short-acting contraceptive methods. Conclusions: This study highlights that substance use and social "stability" of patients contributes to how providers approach their contraceptive counseling and make methods recommendations for their patients with SUDs. More research is needed to understand strategies that individuals with SUDs use to overcome barriers to contraceptive access and adherence in the context of active substance use and social instability.